(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
One of the most modern ways to increase the effectiveness of education among youth today is the effective use of innovative technologies in the educational process. Therefore, research papers are being conducted to develop different projects to create a system of distance education for students using innovative technologies by scientists. In the 21st century, the development of science and information and communication technologies has led to a significant acceleration of the education system. This paper is intended to provide basic information about usage and development of distance education that is crucial for learning new educational technologies.